2009
DOI: 10.1128/iai.01099-08
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of Single Nucleotide Polymorphisms (SNPs) across Mycobacterium bovis Strains and M. bovis BCG Vaccine Strains Refines the Genealogy and Defines a Minimal Set of SNPs That Separate Virulent M. bovis Strains and M. bovis BCG Strains

Abstract: To further unravel the mechanisms responsible for attenuation of the tuberculosis vaccine Mycobacterium bovis BCG, comparative genomics was used to identify single nucleotide polymorphisms (SNPs) that differed between sequenced strains of Mycobacterium bovis and M. bovis BCG. SNPs were assayed in M. bovis isolates from France and the United Kingdom and from different BCG vaccines in order to identify those that arose during the attenuation process which gave rise to BCG. Informative data sets were obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 57 publications
5
53
0
Order By: Relevance
“…In addition, recent studies focusing on M. bovis strains isolated in cattle and badgers from the United Kingdom confirmed the limited number of strains circulating in the United Kingdom, even though the bTB herd prevalence is elevated (14,38). On the other hand, the situation in Belgium is totally opposite: there is a wide diversity of cocirculating strains, with one predominating, and the herd prevalence is under 0.1% in the cattle population (12).…”
mentioning
confidence: 99%
“…In addition, recent studies focusing on M. bovis strains isolated in cattle and badgers from the United Kingdom confirmed the limited number of strains circulating in the United Kingdom, even though the bTB herd prevalence is elevated (14,38). On the other hand, the situation in Belgium is totally opposite: there is a wide diversity of cocirculating strains, with one predominating, and the herd prevalence is under 0.1% in the cattle population (12).…”
mentioning
confidence: 99%
“…In several studies (20,22,53), it has been shown that the NAP7-NAP8 strain type is highly divergent from other strain types and that the C. difficile core genome may be composed of only ϳ1,000 genes (20,22,53,58). To date, MPS and comparative genome analyses of C. difficile have not been applied to the search for additional DNA-based diagnostic targets, as has been done for other human pathogens (6,14,15,28).…”
mentioning
confidence: 99%
“…40 The genealogy of BCG strains is complex and subtle genetic differences, such as single nucleotide polymorphisms, exist between BCG strains and parental M. bovis, which may be responsible for differences in virulence and antigenicity. 41 For example, BCG is unable to utilize L-alanine and this deficiency is thought to inhibit the growth of the vaccine in vivo and limit vaccine efficacy. 42 Loss of this function is due to a point mutation in the BCG gene encoding L-alanine dehydrogenase (Ald) and L-alanine catabolism can be conferred on BCG by introduction of the Ald gene from M. tuberculosis.…”
Section: Review Reviewmentioning
confidence: 99%